The Demographic Consequences of Partition of India (1947) in Punjab - Choubey, Awadh Narayan; Bansal, Taruna (National Geographical Journal of India, 2022)
he advent of Independence in the Indian subcontinent saw some major movements of population and inter-community violence in the country especially in the Punjab province which perhaps witnessed the largest movement of mass population in modern times. Some aspects of this adversity and loss have been explored but most of the studies have not explored the demographic characteristics witnessed by the Punjab region after the partition despite the fact they nearly 9.2 million people were displaced because of this political turmoil. In the present paper we have tried to analyse and study the magnitude of demographic debacle associated with Partition in the state of Punjab.